Ensiling excessively wilted maize stover with biogas slurry: Effects on storage performance and subsequent biogas potential. (June 2020) - Sun, Hui; Cui, Xian; Stinner, Walter; Zhang, Leping; Ju, Xinxin; Guo, Jianbin; Dong, Renjie
Graphical abstract: Highlights: Ensiling wilted maize stover with biogas slurry and effect on BMP were studied. More lignocellulose was degraded in the high buffer-capacity ensiling process. Higher organic-acid content was observed in silages with unseparated biogas slurry. Hetero-lactic-acid bacteria were enriched during storage with biogas slurry. BMP was well-preserved and storage loss completely offset by an enhanced CH4 yield. Abstract: This study evaluated the ensiling performance of excessively wilted maize stover (EWMS) with biogas slurries and the effect on the subsequent biomethane potential. Chicken and pig manure biogas slurries with or without solid-liquid separation were used to amend the stover humidity before ensiling for 60 d. The hetero-lactic-acid fermentative bacteria Atopostipes and Lactobacillus were enriched by the biogas slurry regardless of the solid-liquid separation. Significant increases in the total organic-acid content were observed in silages with chicken (41%) and pig (15%) manure biogas slurries without solid-liquid separation, which was not the case for treatments with solid–liquid separation. During the ensiling process, more lignocellulose was degraded under the high buffer-capacity provided by the ammonia-nitrogen in the biogas slurry. An increase of 7.1%–9.6% was observed for the specific methane yield measured, which offset a storage loss of 5.0%–7.3%. Ensiling EWMS with biogas slurry therefore provides a viable strategy for biogas production.